Reply to “Photoredox Catalysis: The Need to Elucidate the Photochemical Mechanism” - Ghosh, Indrajit (2017)
Spectroscopic measurements and estimated thermodynamic values are important tools for the investigation of photocatalytic reaction mechanisms. However, data derived under idealized conditions fail to capture the complexity of reaction mixtures in preparative organic synthesis.